Horizon scanning in Brazil: outputs and repercussions - Pollyanna Teresa Cirilo Gomes; Verónica Elizabeth Mata; Thais Conceição Borges; Dayani Galato (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To describe the four types of horizon scanning (HS) outputs developed by the National Committee for Health Technology Incorporation (CONITEC) and show their main repercussions on the decision-making processes of the Brazilian Ministry of Health (MH). METHODS: Descriptive study based on participant observation and document analysis of HS outputs (internal reports, alert reports, briefs and sections for CONITEC recommendation reports) developed between January 2014 and July 2018. RESULTS: Fifteen internal reports, six alert reports, two briefs and 57 HS sections were produced. Each output has a specific structure according to its purpose. The methodological approach adopted for developing HS outputs in Brazil is described by EuroScan International Network. The outputs had institutional and international repercussions. The activities resulted in the inclusion of HS as a tool for reducing health lawsuits in the legal framework of the MH. One of the internal reports on a high-cost drug not approved in Brazil for a rare disease was requested by the Health Technology Assessments Network for the Americas (RedETSA), showing the international relevance of the outputs. The HS sections in recommendation reports influenced discussions about incorporating technologies into the Unified Health System. CONCLUSIONS: The developed outputs have purposes ranging from helping build arguments for defense of the MH in cases of health judicialization to inform decision-making processes. In addition, HS sections in recommendation reports have grown in importance recently. CONITEC's HS system has been structured, and its role as a tool to inform health managers has shown to be been relevant.